YCbCr정보와 아다부스트 알고리즘을 이용한 실시간 얼굴검출 시스템 - 김형균(Kim Hyeong gyun); 정기봉(Jung gi bong) (韓國컴퓨터情報學會論文誌, 2008)
In this paper, we converted an RGB into an YCbCr image input from CCD camera and then after compute difference two consecutive images, conduct Glassfire Labeling. We extract an image become ware of motion-change, if the difference between most broad(area) and Area critical value more than critical value. We enforce the detection of facial characteristics to an extracted motion-change images by using AdaBoost algorithm to extract an characteristics. 본 논문에서는 실시간 얼굴검출을 위하여 감시카메라에서 입력된 RGB영상을 YCbCr 영상으로 변환한 후 연속된 두 영상의 차를 구하고 Glassfire 라벨링을 실시했다. 라벨링 결과 가장 넓은 구역의 면적과 Area 임계치 값을 비교하여 임계값 이상의 면적이면 동작변환으로 인식하고 영상을 추출하였다. 이렇게 추출된 동작변환 영상을 대상으로 얼굴 검출을 실시하였다. 얼굴 검출에 필요한 특징을 추출하기 위해 AdaBoost알고리즘을 사용하였다.